POLLUTION LEVEL OF SOME HEAVY METALS IN VEGETABLES PRODUCED THROUGH IRRIGATION FARMING IN GUDINCIN, JIGAWA STATE, NIGERIA - Danladi, Salome Yamishi; Saminu, Murtala Yakasai; Yahaya, Alhaji Adamu (FUDMA JOURNAL OF SCIENCES, 2025)
The pollution level of Chromium (Cr), Cadmium (Cd), Copper (Cu), Lead (Pb) and Zinc (Zn) in Okra, Spinach and Tomato grown in irrigation system of farming in Gudincin Town, Hadejia LGA of Jigawa State was investigated using Atomic Absorption Spectroscopy. The level of metals in the different parts of the vegetables for Okra, Spinach and Tomato are in the order Zn>Cu>Cr>Cd>Pb, Zn>Cr>Cu>Cd> Pb andZn>Cr>Cu>Cd>Pb respectively.  The data obtained showed the translocation of the metals from the agricultural soil into the vegetables. The concentrations of heavy metals in the irrigated soil are in the order Cr>Zn>Cu>Pb>Cd. All the heavy metals in the vegetable samples were found to be within the permissible limit set by Food and Agricultural Organization (FAO) and World Health Organization (WHO).The bioconcentration factor (BCF) of the metals for all the samples were greater than unity (>1)with the exception of Cr (0.946), for spinach and Cr (0.883) for tomato. The translocation factor (TF) value of the metals were all >1 for all the samples with the exception of Pb (0.140) in spinach, indicating translocateton of metals to the aerial parts after absorption. According to the data obtained, tomato, spinach and okra may serve as hyperaccumulators for Zn, Cr, Cd and Cu, whereas spinach can serve as excluder for Pd. Based on the data gathered from the research, the pollution levels of the studied metals in the vegetables was low. Therefore, there is no health concern consuming the vegetables from this farm.
Keywords: Heavy Metals; Irrigation Soil; Tomato; Spinach; Okra; Translocation; Hyperaccumulator